Анализа инфламаторне имуне корелације коагулационог спектра, ПТ, ФБГ, ФДП, Д-Д код аутоимуних болести: Спектар коагулације, ПТ, ФБГ, ФДП, Д-димер код РА и пСС - Zhong, Yinghong; He, Xiao; Geng, Xiufeng; Huang, Heng; Zhang, Zhixian; Ren, Xuezhong; Chen, Hong (Journal of Medical Biochemistry, 2025)
Objective: To investigate the expression of coagulation markers and their correlations with immunological function and inflammation in patients with autoimmune diseases (sjogren’s syndrome and rheumatoid arthritis). Methods: A total of 183 patients were selected for the study: 61 RA patients who made up the RA group were admitted to our hospital between December 2023 and December 2024, 61 pSS patients composed the pSS group, and 61 normal physical examinees who were in the physical examination center of our hospital during the same period composed the control group. Baseline clinical indicators of patients in each group before treatment were collected, including the plasma prothrombin time (PT), international normalized ratio (INR), thrombin time (TT), plasma fibrinogen (FBG), partial thromboplastin time (APTT), fibrinogen degradation products (FDP), and plasma D-dimer (D-D). Results: The expression levels of PT, FBG, TT, FDP and DD in the RA group, the pSS group and the normal group were significantly different. The expression levels of PT, FBG, FDP and D-D in the RA group were all greater than those in the pSS group and the control group. The expression level of PT in the pSS group was greater than that in the control group. The expression levels of PT, FBG, FDP and D-D in the RA group were all greater than those in the pSS group and the control group. The expression level of PT in the pSS group was greater than that in the control group. Analysis of the receiver operating characteristic (ROC) curve showed that, in contrast to those in the normal group, the area under the curve (AUC) of PT in the RA group were 0.638, the AUC of FBG was 0.899, the AUC of FDP was 0.866, and the AUC of D-D was 0.919. The AUC of the combined diagnosis of RA by coagulation indicators was greater than that of the individual detection of each indicator. Compared with that in the normal group, the AUC of PT in the pSS group was 0.618 (P=0.025), and the AUC of TT was 0.645 (P=0.006). The AUC of the combined diagnosis of coagulation indicators for pSS was greater than that of the individual detection of each indicator. Higher D-D in RA patients was significantly linked to higher hs-CRP, CCP, and RF, while higher FBG was significantly linked to higher hs-CRP, ESR, RF, and CCP. Correlation analysis revealed that in the RA group, PT, INR, FBG, FDP, and D-D were positively correlated with CRP and ESR, whereas TT was negatively correlated with CRP and ESR. FBG, FDP and D-D in the pSS group were positively correlated with CRP and ESR. In addition, the coagulation indicators in the RA group were positively correlated with the immune indicators, whereas in the pSS group, they were partially negatively correlated, both of which were significant. In addition, the coagulation indicators in the RA group were positively correlated with the immune indicators, whereas in the pSS group, they were partially negatively correlated, both of which were significant. In patients with pSS, FBG and FDP are positively correlated with hs-CRP, and APTT and FBG are positively correlated with the ESR. Conclusion: Compared with those of pSS, PT, FBG, FDP and D-D have greater reference value for the early diagnosis of RA and the determination of disease severity and can be used as important predictive indicators for the confirmed diagnosis of RA.